The issue of tolerance fostering in the Tyumen region: an attempt of sociological analysis - I А Grosheva; I L Groshev (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2009)
The interaction of ethnic migrants with the local population as well as the analysis of the relations in the receiving social environment is one of the most challenging issues of contemporary sociology. More or less high potential of proneness to conflict which manifests itself in intolerance emerges in the context of interethnic interaction aggravated by migration processes entailing the escalation of social tension, latent and manifest confrontation and conflicts as well.